Determination of Air Quality Protection and Management Strategic Area : Case Study of Tangerang City - Bontong, Septepanus Gala; Permadi, Didin Agustian; Benjamin, Precious (Universitas Diponegoro, 2024)
Metropolitan cities are often associated with anthropogenic activities that affect air quality. Tangerang, as a buffer city in the Greater Jakarta area, needs control strategies to tackle severe air pollution problem. Government Regulation No. 22/2021 requires the establishment of Air Quality Protection and Management Areas (AQPMA) in every city, including Tangerang. The determination of AQPMA involve emissions inventories, air quality, population density, land use, and meteorological conditions, using secondary data and air quality modeling with AERMOD. The results of the emission inventory show that the largest contribution comes from the manufacturing and road transportation industries, with NOx 19,747, CO 556,341, PM10 27,001, PM2.5 22,080, SO2 2,233, and NMVOC 295,482 (in Gigagrams/year). The result of the air model then accordance with measurements at AQMS Pasir Jaya in 2022. The average annual concentration results at this station are NOx 35, CO 1,200, PM10 38, PM2.5 39, and SO2 7.5 (in μg/m3). Ciledug is the sub-district with the highest population density, which is 19,233 people/km2. Based on AQPMA scores, eight very high-risk sub-districts must be a priority in mitigating clean air in Tangerang. A similar approach can be used in other cities to map vulnerability to air pollution as mandated by AQPMA.